2003
DOI: 10.1007/s10008-002-0296-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization and electrochemical lithium insertion properties of carbon nanotubes prepared by the catalytic decomposition of methane

Abstract: Carbon nanotubes (CNTs) were synthesized by the catalytic decomposition of methane at 773, 873 and 973 K. Structures of these carbon nanotubes were characterized by TEM, HRTEM, XRD and Raman spectra, respectively. The results showed that with the increase of preparation temperature, the d(002) value of the CNTs decreased, while the L-a values and the degree of crystallihity of the samples increased. Electrochemical lithium insertion properties of the CNTs used as positive electrodes in CNTs/Li cells were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It was assumed that the central cores of MWNTs played a role in the accumulation of Li ions as well as in the creation of an electrical double layer, and hence their closing with thermal treatment and the formation of continuous carbon layers were unfavourable for lithium absorption. Similarly, Wu et al [124] studied the structure and lithium insertion behaviour of MWNTs grown at different temperatures by the catalytic decomposition of methane. It was found that the lithium storage capacity of the MWNTs decreased with an increase in the growth temperature.…”
Section: Theoretical Investigationsmentioning
confidence: 99%
“…It was assumed that the central cores of MWNTs played a role in the accumulation of Li ions as well as in the creation of an electrical double layer, and hence their closing with thermal treatment and the formation of continuous carbon layers were unfavourable for lithium absorption. Similarly, Wu et al [124] studied the structure and lithium insertion behaviour of MWNTs grown at different temperatures by the catalytic decomposition of methane. It was found that the lithium storage capacity of the MWNTs decreased with an increase in the growth temperature.…”
Section: Theoretical Investigationsmentioning
confidence: 99%